Genetic analysis of first lactation production and fertility traits in Karan Fries cattle - DASH, S K; GUPTA, A K; SINGH, AVTAR; CHAKRAVARTY, A K; MOHANTY, T K; PANMEI, A; SHIVAHRE, PUSHP RAJ (The Indian Journal of Animal Sciences, 2016)
The present investigation encompasses the genetic analysis of first lactation production and fertility performance of Karan Fries cattle. Data were collected on 1,988 cows maintained at National Dairy Research Institute (NDRI), Karnal, Haryana over a period of 34 years (1978 to 2012). Least squares analysis was carried out to study the effect of non-genetic factors, viz. season of first calving (SC), period of first calving (PC), genetic group (GG) and age at first calving group (AFCG) on first lactation fertility and production traits. Least squares means of age at first calving (AFC), first calving to first service (FCFS), first service period (FSP), first lactation length (FLL), first calving interval (FCI), first lactation 305 day or less milk yield (F305MY), first lactation total milk yield (FTMY), milk yield per day of first lactation length (MY/FLL), milk yield per day of first calving interval (MY/FCI) and first lactation daughter pregnancy rate (FDPR) were 957.48±6.54 days, 79.46±3.58 days, 130.03±4.43 days, 347.02±5.51 days, 415.47±5.21 days, 3,213.91±47.61 kg, 3,760.49±74.27 kg, 10.49±0.12 kg/day, 9.14±0.13 kg/ day and 0.33±1.42, respectively. Overview of least squares analysis regarding first lactation traits indicated that most of the non-genetic factors excepting AFC group, significantly affected the performance of the animal. Results revealed the superiority of F1 over other GG of Karan Fries cows indicating a significant effect of heterosis. Heritability estimated by both analysis of variance and average information restricted maximum likelihood methods indicated that the fertility traits were less affected by additive gene action; the estimates for production traits indicated higher role of additive gene action. Both phenotypic and genetic correlation estimates indicated antagonistic association between fertility and production traits.